Evaluation of Thyroid Hormones in Women Patients with Recurrent Miscarriage - Haitham Sachet Hamadi; Ahmed Mohammed Zheoat (American Journal of Biomedicine and Pharmacy, 2025)
Recurrent miscarriage is defined as the loss of two or more consecutive pregnancies before 20 weeks of gestation. This condition results from multiple factors, including genetic, hormonal, anatomical, immunological, and environmental influences. This study investigates the role of thyroid hormone levels (T3 and T4) and body mass index (BMI) in recurrent miscarriage women. A total of 190 women aged 20–44 years were studied. Participants were divided into two groups: 82 women with successful pregnancies (Standard group) and 108 women with three or more recurrent miscarriages (Recurrent miscarriage group). Results showed no significant difference in age between the groups (p = 0.0896). However, BMI was significantly higher in the recurrent miscarriage group (25.25 ± 0.360) than in the standard group (23.73 ± 0.423, p = 0.0068). T4 levels were lower in the recurrent miscarriage group (62.76 ± 2.487 nmol/L) compared to the standard group (70.66 ± 2.397 nmol/L, p = 0.0267). T3 levels did not significantly differ between groups (p = 0.2587). These findings suggest that elevated BMI and reduced T4 levels may contribute to recurrent miscarriage risk. Addressing these factors may improve pregnancy outcomes.